Solitary osteochondroma of the elbow causing ulnar nerve compression: a case report - Karakurt, Lokman; Yilmaz, Erhan; Varol, Tahir; Ozdemir, Hüseyin; Serin, Erhan (My University, 2004)
We report ulnar nerve compression caused by solitary osteochondroma of the right elbow in a 34-year-old man. Two osteochondromas were detected originating from the olecranon and medial humeral epicondyle, respectively. The patient had severely restricted elbow motion, pain, and hypoesthesia of the forth and fifth fingers. The lesions were surgically removed, together with subcutaneous anterior transposition of the ulnar nerve. At the end of the postoperative eight months, complaints of the patient disappeared except for slight hypoesthesia in the fingers. Literature search revealed only a single case of solitary osteochondroma associated with peripheral nerve compression.
Dirsekte soliter osteokondroma bagli gelişen ulnar sinir basisi: olgu sunumu.
Keywords: Adult; Bone Neoplasms; Diagnosis, Differential; Elbow Joint; Humans; Male; Nerve Compression Syndromes; Osteochondroma; adult; article; bone tumor; case report; differential diagnosis; elbow; human; male; nerve compression; osteochondroma; pathology; radiography